Standardy unijne a realizacja informacyjnej roli menedżerów w przedsiębiorstwach przemysłu spożywczego - Gableta, Małgorzata; Cierniak-Emerych, Anna (European Union's Requirements and the Realization of Information Function of Managers in Food Processing Enterprises, 2005)
In this paper there are presented issues of the information function of managers in view of European Union's requirements. The research was carried out in Polish food processing enterprises. The empirical results point out at existing state of standard problems connected with information function of managers. The work also attempts at determining directions of activities to solve these problems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 219-223